Investigation into the mechanical behavior of a polymer optical fiber embedded in a structural adhesive. (September 2022) - Weiland, J.; Bartholomee, W.; Luber, M.; Schiebahn, A.; Engelbrecht, R.; Reisgen, U.
Abstract: To guaranty a safe load transfer through adhesively bonded joints, Structural Health Monitoring (SHM) methods that allow for permanent monitoring of the structural bond condition, are becoming more and more important. To meet this increasing demand, a novel approach for SHM of adhesively bonded joints by use of integrated Polymer Optical Fibers (POF) has been demonstrated in previous work. The sensor operating principle is based on strain transfer from the structural adhesive to the integrated POF. This strain transfer leads to a deformation of the POF cross-sectional shape and in that way affects the optical light propagation in the POF. In the current work, numerical and experimental results are presented into the mechanical behavior of embedded POF in adhesive bulk specimens subjected to tensile loading. Local deformations of both the POF (Asahi Kasei DB 500) and the structural adhesive (3 M Scotch Weld DP410) are evaluated using Digital Image Correlation (DIC). In the loading direction, a linear correlation is shown between strain inside the POF core and strain of the surrounding adhesive. Tests results, as well as fracture analysis, show a highly ductile behavior and failure of the POF cladding material and the interface between the POF core and annular cladding.